Pelatihan Guru Dan Sosialisasi Literasi Numerasi Untuk Meningkatkan Pengajaran Di SDN 1 Wonolelo Kabupaten Magelang Provinsi Jawa Tengah: (Teacher Training and Numeracy Literacy Socialization to Improve Teaching at SDN 1 Wonolelo, Magelang Regency, Central Java Province) - Tri Yusnanto; Azzhura Rizqia Nada; Benedicta Westri Talenta Ekaristia; Mila Dianurt; Ratih Vicha Anggraeni; Zulia Maharani (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Around 2022, the Merdeka Curriculum can be implemented in all educational units, including but not limited to the Movement School. These include I and IV classes of TK-B, SD and SDLB, VII class of SMA and SMPLB, VIII class of High School and SMALB, and X class of SMK. Furthermore, since 2021, the UN has been converted to the Minimum Competence Assessment (AKM), which includes literacy, literacy using mathematics (numeration). For 18 years, Indonesia has remained in the lowest 10th place on PISA and TIMSS in terms of literacy, numeration, and science. Since literacy and numeration skills are indicators in AKM and PISA assessments, teachers must have the teaching skills needed to meet this independent curriculum. When teachers master literacy and numeration, they can convey material clearly and correctly. Teachers are expected to innovate to enhance students' abilities through a range of lessons with a student-centred learning approach. The servants collaborated with SDN 1 Wonolelo in the activities of this community partnership program. During the dedication program, teachers acquire literacy and numeration knowledge that is useful to enhance their literate and numerational skills. The benefits of this training include: (1) teachers become familiar with questions oriented to literacy and numeracy; (2) teachers can prepare a Learning Implementation Plan (RPP) with the integration of literacy and numeracy according to the Independent Curriculum; (3) the culture of literacy and numeracy at SD Negeri 1 Wonolelo has become active again.